2023
DOI: 10.1080/26410397.2023.2204025
|View full text |Cite
|
Sign up to set email alerts
|

Developing the menstrual justice agenda: insights from a mixed method study in the mid-western region of Nepal

Abstract: This article develops the concept of “menstrual justice”. The legal scholar Margaret E. Johnson has developed an expansive approach to menstrual justice incorporating rights, justice, and a framework for intersectional analysis, with a focus on the US. This framework provides a welcome alternative to the constrictive and medicalised approaches often taken towards menstruation. However, the framework is silent on several issues pertaining to menstruation in Global South contexts. This article therefore develops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Our results indicate that Nepal continues to bear a disproportionate burden of menstrual-related discrimination, which manifest as exclusions from participating in social and religious activities. These findings are consistent with recent studies, which showed that Chhaupadi is most prevalent among the Brahmin/Chhetri ethnic community in the mid-western part of Nepal (Amery et al, 2023; Thakuri et al, 2021; UNFPA, 2019; UNICEF, 2020, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results indicate that Nepal continues to bear a disproportionate burden of menstrual-related discrimination, which manifest as exclusions from participating in social and religious activities. These findings are consistent with recent studies, which showed that Chhaupadi is most prevalent among the Brahmin/Chhetri ethnic community in the mid-western part of Nepal (Amery et al, 2023; Thakuri et al, 2021; UNFPA, 2019; UNICEF, 2020, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, our study contributes valuable insights into the complexity of menstrual health challenges in Nepal, shedding light on the spatial patterns and determinants of menstrual discriminatory practices. By elucidating the geographical variations, our findings provide a foundation for targeted community based interventions such as the cultural behaviour change education (Amery et al, 2023; Thapa et al, 2019; Thomson et al, 2019). The identification and prioritization of vulnerable populations are crucial steps toward dismantling the deeply rooted beliefs and promoting a more inclusive and equitable society.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation